Chronic features of allergic asthma are enhanced in the absence of resistin-like molecule-beta - LeMessurier, Kim S. (Sci Rep, 2018)
Asthma is characterized by inflammation and architectural changes in the lungs. A number of immune cells and mediators are recognized as initiators of asthma, although therapeutics based on these are not always effective. The multifaceted nature of this syndrome necessitate continued exploration of immunomodulators that may play a role in pathogenesis. We investigated the role of resistin-like molecule-beta (RELM-β), a gut antibacterial, in the development and pathogenesis of Aspergillus-induced allergic airways disease. Age and gender matched C57BL/6J and Retnlb(−/−) mice rendered allergic to Aspergillus fumigatus were used to measure canonical markers of allergic asthma at early and late time points. Inflammatory cells in airways were similar, although Retnlb(−/−) mice had reduced tissue inflammation. The absence of RELM-β elevated serum IgA and pro-inflammatory cytokines in the lungs at homeostasis. Markers of chronic disease including goblet cell numbers, Muc genes, airway wall remodelling, and hyperresponsiveness were greater in the absence RELM-β. Specific inflammatory mediators important in antimicrobial defence in allergic asthma were also increased in the absence of RELM-β. These data suggest that while characteristics of allergic asthma develop in the absence of RELM-β, that RELM-β may reduce the development of chronic markers of allergic airways disease.